So what brings you to the clinic today?' : talk in family intake interviews - Jardine, Jennifer (Department of Psychology, 2014)
This research examined the ways in which families constructed presenting problems in the talk of their first session at a psychology clinic. It also looked at the ways in which they constructed individual subjectivities during the interviews. Six families self-selected for therapy and were then invited to participate in the study. The analysis was based on the clinical interviews undertaken by therapists.